PERANCANGAN KINCIR ANGIN SUMBU HORIZONTAL UNTUK PEMOMPA AIR LAUT KE LAHAN GARAM - Bambang Setiawan; Rusita Rusita (University of Muhammadiyah Jakarta, 2015)
Salt is one of the strategic commodities, as well as the consumption, is a complement of the need for food is also an industrial chemical raw materials, raw material in the salt production, especially seawater for salt crystallization process with the help of sunlight (solar evaporation). To meet the needs of the seawater, seawater must be transferred from seawater irrigation canal (ditch) to salt farms, so that the needs tools for pumping seawater from seawater irrigation canal (ditch) to salt farms, one of which is by using a windmill. However, declining salt farmers productivity is caused by seawater supply is interrupted due to the windmills that existed at this time, can only operate at high wind speeds because the blades are used by salt farmers too weight, so that windmills can operate at lower wind speeds, can be done by drilling a very small hole in the piston and designing windmill blades lighter. By designing windmills for pumping seawater into salt farm has resulted pumping capacity of 83,59 m3/day in order to meet the daily needs of seawater for the salt production process by 67 m3/day.